A Comprehensive Overview of Antibiotic Selection and the Factors Affecting It - Patel, Karan (Cureus, 2021)
In order to prescribe an antibiotic, a physician must go through a series of decision-making processes that involve both the drug and the host. In this review article, we outline exactly what those decision-making processes are and some of their limitations. Before a medication can be prescribed, a physician has to determine if the antibiotic works against the host pathogen. To do this, basic science techniques are employed including phenotypic methods such as broth dilution methods, Kirby-Bauer susceptibility testing, Epsilometer test (E-test), and genotypic methods such as the new and upcoming automated tests. After determining if a drug has potential to work, the physician must consider the drug’s mechanism of action in order to determine a dosing regimen. Some groups of drugs should be administered at high concentrations infrequently, others should be given more frequently in smaller doses, and others lie somewhere between this spectrum. Finally, external factors such as the patient's age, especially for pediatrics and geriatrics patients, need to be considered, as these groups have the highest health care burden but are among the most vulnerable when it comes to the side effects of drugs.